Delta13Carbonate chemostratigraphy of the Carrapateira Outlier (Lower Kimmeridgian) Southern Portugal - Borges, Marisa (2015)
Mineralogical Magazine, Vol. 75 (3), 2011, Goldschmidt Conference Abstracts